PERTANGGUNGJAWABAN PEMEGANG SAHAM PERSEROAN TERBATAS MELALUI INDIKATOR ALTER EGO DALAM PENERAPAN DOKTRIN PCV DI INDONESIA - Gideon Paskha Wardhana (Refleksi Hukum: Jurnal Ilmu Hukum, 2021)
This research aims to understand the purpose of the adaption of the alter ego as an indicator to the doctrine of piercing the corporate veil (PCV) and the concept of personal liability in Act No. 40 of 2007 on Limited Liability Company (LLA 2007). In addition, this research will evaluate the effectiveness of the legal protection that is given through the implementation of the alter ego. This juridical and normative research uses literature and qualitative research method on the secondary resources. The research result shows that the responsibility of shareholders in a limited company (PT) is limited to the number of shares they have in the company. Currently, this characteristic of limited liability and separate legal entities is often misused to create a shield for shareholders so that they can avoid being personally liable for their illegal acts. To prevent this deviant practice, the PCV doctrine, which acts as an exception to the principle of limited liability, has been adopted by the LLA 2017. However, the PCV doctrine is only partially adopted. Likewise with the alter ego is an indicator, which is ineffective and rarely used.